2014
DOI: 10.3109/13697137.2014.900746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbal preparations on symptom clusters during the menopausal transition

Abstract: Black cohosh mixed with other herbals, Rheum rhaponticum, and French maritime pine bark had significant effects on hot flushes and at least one other symptom. These herbal therapies may be a promising alternative treatment to hormonal treatment. Future studies should classify women based on their menopausal stages, report each symptom separately, have adequate sample size, focus on multiple co-occurring symptoms, and target symptom management of menopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…While hormone replacement therapy (HRT) effectively reduces vasomotor symptoms associated with the decrease of estrogen levels during menopause, results of the Women's Health Initiative (WHI) trial indicated that the benefits of HRT did not outweigh the risks 3 , as estrogen alone would increase risks of stroke and venous thromboembolism (VTE), and together with progestin could incur additional risks of causing breast cancer and heart attack. As a result, the role of HRT has been limited to treat postmenopausal symptoms at minimal dose and duration, and more efficacious and better tolerated alternatives to decrease menopausal symptoms are still being sought 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…While hormone replacement therapy (HRT) effectively reduces vasomotor symptoms associated with the decrease of estrogen levels during menopause, results of the Women's Health Initiative (WHI) trial indicated that the benefits of HRT did not outweigh the risks 3 , as estrogen alone would increase risks of stroke and venous thromboembolism (VTE), and together with progestin could incur additional risks of causing breast cancer and heart attack. As a result, the role of HRT has been limited to treat postmenopausal symptoms at minimal dose and duration, and more efficacious and better tolerated alternatives to decrease menopausal symptoms are still being sought 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…13, 810 These co-occurring symptoms are typically not assessed or are considered secondary outcomes, with few trials specifically targeting more than one symptom. 6, 7, 11, 12 Research shows that symptoms act synergistically and that the impact of co-occurring symptoms on an individual is multiplicative rather than additive. 9, 13 Thus, addressing multiple co-occurring symptoms is vital to improving midlife women’s quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 Cochrane review of randomized controlled trials assessing black cohosh versus placebo or other treatments found that black cohosh did not significantly reduce hot flashes or menopausal symptom scores, whereas hormone treatment (compared to black cohosh) reduced symptom scores significantly [ 13 ]. A 2015 extensive review of effects of herbal preparations on symptom clusters in menopause suggested that black cohosh had a significant effect on hot flashes [ 22 ], but this observation was based on qualitative review of the research, rather than the more rigorous quantitative methods used in the Cochrane review of randomized trials [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black cohosh has been suspected of being linked to liver disorders, although cases are rare and can seldom be attributed directly to black cohosh [ 14 ]. Evidence on safety of black cohosh from the Cochrane review was inconclusive because of inadequate reporting [ 13 ], and the more recent review suggested that the incidence of adverse effects associated with black cohosh did not differ from those associated with placebo [ 22 ].…”
Section: Discussionmentioning
confidence: 99%